Teacher professional learning through pedagogy of discomfort. Issue 6 (2nd November 2018) - Nolan, Andrea; Molla, Tebeje
ABSTRACT: The established link between quality early childhood programs and positive child trajectories has led to the professionalization of the early childhood workforce in Australia. Attention has concentrated on the upgrading of qualifications and opportunities for professional learning. This paper focuses on exploring teacher professional learning, positioning it as a reflective practice. It considers teacher dispositions, moments of disjuncture and how these influence teacher learning. Theoretically, the paper is informed by Bourdieu's concepts of habitus and reflexivity; Mezirow's theory of transformative learning; and Boler and Zembylas's notion of pedagogy of discomfort. The data are drawn from a statewide mentoring project for newly graduated early childhood teachers in Victoria, Australia. The findings suggest that for teacher professional learning to be transformative, the process must be informed by a pedagogy of discomfort thereby considering the interplay of teachers' professional dispositions, experiences of disjuncture, and acts of deliberation.